Gonadal Degeneration and Hepatopancreas Alteration in Orange Mud Crab Scylla olivacea Infected With Sacculina beauforti (Crustacea; Rhizocephala; Sacculinidae) - Fazhan, Hanafiah; Waiho, Khor; Glenner, Henrik; Moh, Julia Hwei Zhong; Hassan, Marina; Ikhwanuddin, Mhd (Frontiers in Marine Science, 2020)
Infestation of Sacculina beauforti on an aquaculture species, mud crab Scylla olivacea is alarming due to its high prevalence and the extreme morphological changes in hosts. To further understand its pathological effect on growth and reproduction of S. olivacea, gonadal and hepatopancreatic histological changes of infected individuals were compared with healthy individuals. Also, the histological characteristics of S. beauforti’s mature externa was described. Hepatopancreases of infected individuals were loosely packed and rootlets were observed in the intertubular spaces. Although hepatopancreatic tubule count was significantly lower, tubule diameters were unaffected. Gonads, however, were severely affected. No germ cells were found in the infected testes (except for remnants of spermatozoa), indicating the arrest of spermatogenesis. Rootlets were also present in testes of infected individuals. Ovarian tissues of infected females were severely damaged with no rigid cell structures. Gonadosomatic index (GSI) of infected males and females were lower, but the hepatosomatic index (HSI) were higher than their healthy counterparts. No significant differences in GSI and HSI values were observed among infected males and females. Multiple regression analysis revealed that carapace width, GSI and HSI are statistically important for the prediction of infection status. Given the high prevalence of S. beauforti infection and its disruptive effects on the morphology and internal physiology of S. olivacea, this study, albeit fundamental and incomprehensive, highlights to farmers and researchers the emergence of a castrating parasite and the urgency for the development of preventive measures and treatments for this disease in an economically important aquaculture species.